Prototyping and Piloting the Flexi Hose for Onshore and Offshore Pipeline Rehabilitation - Tony, Charles Runyaam (IRC, 2021)
Pipelines have been described as the most efficient and widely used transport medium for moving fluid, in particular oil and gas.